Direct comparison between millifluidic and bulk-mixing platform in the synthesis of amorphous drug-polysaccharide nanoparticle complex - Dong, Bingxue (2020)
Amorphous drug-polysaccharide nanoparticle complex (or drug nanoplex) had emerged as an ideal supersaturating delivery system of poorly-soluble drugs attributed to its many attractive characteristics. Herein we presented for the first time direct comparison between two nanoplex synthesis platforms, i.e. millifluidics and bulk mixing, representing continuous and batch production modes, respectively. They were compared by the resultant nanoplex’s (1) physical characteristics (size, zeta potential, and payload), (2) preparation efficiency, (3) storage stability, (4) dissolution rate/supersaturation generation, and (5) production consistency. The effects of key variables in drug-polysaccharide complexation (pH, charge ratio) were investigated in both platforms. Perphenazine and dextran sulfate were used as the drug and polysaccharide models, respectively. The results showed that both platforms shared similar dependences on pH and charge ratio with similar optimal preparation conditions, where the pH was the governing variable through its influence on size and zeta potential, Nanoplexes having mostly similar characteristics (size %70–90 nm, zeta potential %"50 mV) were produced by both platforms, except for the payload where bulk mixing resulted in lower payload (65% versus 85%). The lower payload, however, resulted in its superior supersaturation generation. Nevertheless, millifluidics was favored attributed to its superior production consistency and scalability.